تحليل مشكلات الطالبات في تعلم مفردات اللغة العربية : دراسة وصفية في الصف الأول المتوسط بالمدرسة الإسلامية أولو النهى ميدان جوهور - Hasibuan, Fina Rizkiah (Lembaga Yasin AlSys, 2024)
The research questions are: What are the problems of female students in learning the Arabic language vocabulary in the first grade at the Islamic School Ulu Al-Nuha, Johor Square, and what are the solutions from the school to the students’ problems in learning the Arabic language vocabulary in the first grade at the Islamic School, Ulu Al-Noha, Johor Square. The method used is qualitative descriptive research of the type of field research, using the observation and interview method in collecting data. The results of this research are summarized as follows: (1) The problems of female students in learning the vocabulary of the Arabic language are that they rarely use the Arabic language and are not accustomed to using the Arabic language because they do not have the courage, less ability to allocate time between memorizing vocabulary and memorizing the Qur’an, difficulty in memorizing the vocabulary that They were not used to hearing it. (2) The school’s solutions to the students’ problems in learning Arabic vocabulary are to consider the students’ learning methods in choosing learning methods. The students try to get used to using the daily Arabic language with vocabulary. The school gives daily assignments to the students to memorize the vocabulary on the day. The school gives daily assignments that give The school gives the students vocabulary words and then sticks them on the bulletin board or in front of the classroom door to make it easier for the students to remember the vocabulary words.